Comparative safety of dolutegravir-based or efavirenz-based antiretroviral treatment started during pregnancy in Botswana: an observational study. Issue 7 (July 2018) - Zash, Rebecca; Jacobson, Denise L; Diseko, Modiegi; Mayondi, Gloria; Mmalane, Mompati; Essex, Max; Gaolethe, Tendani; Petlo, Chipo; Lockman, Shahin; Holmes, Lewis B; Makhema, Joseph; Shapiro, Roger L
Summary: Background: Global rollout of dolutegravir-based antiretroviral therapy (ART) has been hampered in part by insufficient safety data in pregnancy. We compared birth outcomes among women initiating dolutegravir-based ART with those among women initiating efavirenz-based ART in pregnancy in Botswana. Methods: In this observational study, we captured birth outcome data at eight government hospitals throughout Botswana (~45% of all deliveries in the country) in an ongoing study that started on Aug 15, 2014. In 2016, Botswana changed first-line ART from efavirenz-tenofovir-emtricitabine to dolutegravir-tenofovir-emtricitabine, including for pregnant women. This analysis includes women starting either efavirenz-based ART or dolutegravir-based ART during singleton pregnancy (regimen started and delivery occurring between Aug 15, 2014, and Aug 15, 2016, for efavirenz-based ART and between Nov 1, 2016, and Sept 30, 2017, for dolutegravir-based ART). We excluded births to mothers who had switched regimen or stopped ART. The primary outcomes were the combined endpoints of any adverse outcome (stillbirth, preterm birth [<37 weeks' gestation], small for gestational age [SGA; less than the tenth percentile of birthweight by gestational age], or neonatal death [within 28 days of age]) and severe adverse outcomes (stillbirth, neonatal death, very preterm birth [<32 weeks' gestation], and very SGA [less than the third percentile of birthweight by gestational age]). We fitted log-binomial regression models, controlling for maternal age, gravidity, and education, to estimate adjusted risk ratios (aRRs). Findings: Our analysis included 1729 pregnant women who initiated dolutegravir-based ART and 4593 who initiated efavirenz-based ART. The risk for any adverse birth outcome among women on dolutegravir versus efavirenz was similar (33·2% vs 35·0%; aRR 0·95, 95% CI 0·88–1·03), as was the risk of any severe birth outcome (10·7% vs 11·3%; 0·94, 0·81–1·11). We found no significant differences by regimen in the individual outcomes of stillbirth, neonatal death, preterm birth, very preterm birth, SGA, or very SGA. Interpretation: Adverse birth outcomes were similar among pregnant women who initiated dolutegravir-based and efavirenz-based ART. Dolutegravir-based ART can be safely initiated in pregnancy. Funding: National Institutes of Health.